Tissue engineering applications in periodontics: Alternate god - Samir Chugh; Nupur Arora (Wolters Kluwer Medknow Publications, 2014)
"Tissue engineering" also referred as regenerative medicine indicates a new interdisciplinary initiative, which has the goal of growing tissues or organs directly from a single cell taken from an individual. Originally coined to denote the construction in the laboratory of a device containing viable cells and biologic mediators in a synthetic or biologic matrix that could be implanted in patients to facilitate regeneration. However, the term has crept into clinical armory of periodontists and has attained certain halo and glamour even when used in mundane and prosaic situations. Thus, this paper critically evaluates its role and application in clinical scenario.